Emergency of Edge city between Regeneration and Acclimatization Urban - Yassin jasim, zainab; Hassan Jasim, Adel (Journal of Planner and Development, 2023)
In the nineteenth century, a new type of cities appeared, known as new cities located on the edges of major cities, and these cities began to  decentralization, urban studies turned to this type of cities to find out the most important reasons for the emergence of new cities and find out what those cities will become . Therefore, we will discuss in this research how the urban emergence of these cities (edge cities) occurs, so the research formulates its problem : The need to know the stages that edge cities go through, ending with their emergence, and the mechanisms that cities take within their context  ( regeneration or adaptation ), Assuming that edge cities are a dynamic system that goes through several stages, ending with the emergence stage , this research is to know the stages that lead to the emergence of these cities and to know the mechanism of the city's behavior within its context (regeneration or adaptation ) The researcher also touched on the concept of the dynamic system and knowledge of the stages of the dynamic system, so that the researcher came to the most important vocabulary that resulted from the Association of the vocabulary of the edge cities with the vocabulary of the dynamic system, namely the indicators of urban emergence, its pattern, indicators of regeneration and adaptation and the application of these indicators applying the emerging pattern indicators for  Al-madayin city and indicators of regeneration and adaptation .